2013
DOI: 10.1016/j.polymer.2012.11.075
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and orientation behavior of polystyrene-b-polybutadiene-b-poly(methyl methacrylate) triblock terpolymers: Influence of polybutadiene microstructures and the molar masses

Abstract: Morphological changes caused by deformation and orientation of different domains of polystyrene-b-polybutadiene-b-poly(methyl methacrylate),SBM, triblock terpolymers were investigated using in-situ small angle X-ray scattering (SAXS), tensile testing, and transmission electron microscopy (TEM). Two sets of SBM triblock terpolymers with similar weight fractions of the three blocks were studied. The two sets differ in terms of their molecular weights. Each set contained two SBM differing in their polybutadiene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We here report the supramolecular blending of a polymer A with another polymer C leading to the newly formed noncovalently linked polymer AB′C, where the middle segment B′ represents a supramolecular linker, segregating from both the A- and the C-block of the molecule (see Figure ). Although covalently linked ABC triblock terpolymers are the prototype of a polyphilic system well-known to microphase separate via, for example, hydrophilic/fluorophilic/hydrophobic interactions, the inclusion of directed supramolecular interactions as part of a polyphilic segregation has not been addressed yet. The formation of nanostructured compartments of supramolecular polymers driven by noncovalent forces thus presents a novel concept toward multicompartment micelles. …”
mentioning
confidence: 99%
“…We here report the supramolecular blending of a polymer A with another polymer C leading to the newly formed noncovalently linked polymer AB′C, where the middle segment B′ represents a supramolecular linker, segregating from both the A- and the C-block of the molecule (see Figure ). Although covalently linked ABC triblock terpolymers are the prototype of a polyphilic system well-known to microphase separate via, for example, hydrophilic/fluorophilic/hydrophobic interactions, the inclusion of directed supramolecular interactions as part of a polyphilic segregation has not been addressed yet. The formation of nanostructured compartments of supramolecular polymers driven by noncovalent forces thus presents a novel concept toward multicompartment micelles. …”
mentioning
confidence: 99%
“…They concluded that this behavior was governed by the relatively weak incompatibility of the end blocks PS and PMMA in comparison to the strong incompatibility of PB block. Kabir et al [7] studied the morphological changes caused by the deformation and orientation of different domains, analyzing the influence of PB isomers (1,2 or 1,4). In the case of 1,2 isomercontaining SBM triblock copolymer, a co-existing lamellar and cylindrical morphology of PB block was observed, while for 1,4 isomer-containing one, only well segregated lamellar patterns were found.…”
Section: Introductionmentioning
confidence: 99%